Implementation of Multicultural Values in Diversity of a Multiethnic School (A Case Study: Kuncup Melati Junior High School, Semarang) - Rizqiyawati, Ika; Rusdarti, Rusdarti; Eko Pramono, Suwito (JESS (Journal of Educational Social Studies), 2020)
Kuncup Melati Junior High School (JHS) is a multiethnic school whose students come from Chinese and Javanese ethnic groups. Both groups have a negative stereotype towards one another and often engage in conflicts. The school opens a room for discussion for both groups, proving that both can coexist in diversity. This study aims to analyze the symbolic interactionism and the implementation of multicultural values. Data analysis technique used were qualitative technique, borrowing the symbolic interactionism theory of Herbert Blumer. The informants were the teachers, the Chinese students, and Javanese students. The data collection technique employed in-depth interview, observation, and documentation study. The results revealed that the symbolic interactionism between two groups can be interpreted from multiethnic friendship and understanding of each other’s culture and religion. This can reduce the stereotype between two groups, and in turn, result in respect from one another. The heterogeneous school environment showcasing the implementation of respect for one another is indirectly internalized in students’ behavior. Multicultural values found in Kuncup Melati JHS are tolerance, solidarity, and equality. This study recommends to open a more diverse multietchnic and multifaith interaction because multicultural values cannot only be taught in class, but rather have to be experienced personally.